Pesan Moral Dalam Film “KKN Di Desa Penari” (Analisis Semiotika Roland Barthes) - Sasa, Nadya Dwi Safitri; Masruroh, Dorifatul (Program Studi Ilmu Komunikasi, 2024)
Films can provide education or motivation from the messages in them. Even horror films must have messages that can be taken as motivation. One of them is KKN in the Dancer Village. This film tells about students at a university in East Java who are conducting Community Service Program (KKN) in a dancer village. They carry out KKN in a village that is located in the middle of a forest and is the only village where there will certainly be many mystical phenomena and traditional customs that are inversely proportional to the habits of the city's students. From the phenomenon of the film, the researcher examines more deeply the messages and meanings in the film with a study entitled